Influence of Methotrexate on circulatory levels of T lymphocyte-related cytokines in patients with moderate to severe plaque psoriasis - Bei-bei SU; Quan GAN; Cai-bin GAN (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2020)
Objective: To explore the changes in expression levels of T-cell related cytokines, including IFN-γ, IL-4, IL-17a, IL-21 and TGF-β, in peripheral blood of responders and non-responders after 16 weeks of Methotrexate (MTX) treatment. Methods: A total of 49 responders, 13 non-responders and 35 healthy controls were enrolled in this study. Pearson analysis was used to determine the correlation between PASI scores and serum IFN-γ, IL-4, IL-17a, IL-21 and TGF-β levels in psoriatic patients before the treatment. Following the treatment, biochemical markers and serum levels of IFN-γ, IL-4, IL-17a, IL-21, and TGF-β were compared among responders, non-responders and normal controls. Results: After 16-week treatment, psoriatic patients displayed significantly higher serum levels of creatinine, uric acid, urea nitrogen, ALT and AST (P<0.05 for all vs. pretreatment). Treatment with MTX markedly lowered serum levels of IFN-γ [(749.03±76.77) pg/mL vs. (953.69±101.58) pg/mL], IL-17a [(756.96±101.73) pg/mL vs. (963.75±64.38) pg/mL], and IL-21 [(514.76±53.48) pg/mL vs. (693.45±87.91) pg/mL] (P<0.05 for all vs. pretreatment), while increasing TGF-β [(433.59±65.39) pg/mL vs. (298.36±77.83) pg/mL, P<0.05] in the responder group. However, the serum levels of IL-4 did not change significantly [(218.72±67.39) pg/mL vs. (198.78±47.71) pg/mL]. In contrast, MTX treatment did not significantly alter serum levels of cytokines in the non-responder group (all P>0.05). Prior to the treatment, PASI scores correlated with IFN-γ, IL-17a, IL-21 and TGF-β, with coefficient of 0.25, 0.75, 0.66, -0.11, respectively (P<0.05 for all). Conclusion: The potential mechanism of MTX in alleviating psoriasis may be via the improvement of the balance of Th1/Th2 and Th17/Treg.